(untitled) (Global Journal of Science Frontier Research, 2018)
On the basis of studying of genes new properties of a genetic code were established and its major integrated characteristics are calculated Two groups of such characteristics were allocated The first group treats integrated characteristics for the DNA areas where genes are in pairs blocked and all 5 cases of the overlappings allowed by structure of DNA were investigated The second group of characteristics treats most DNA extended areas in which there are no genetic overlappings The interrelation of the established integrated characteristics in the called groups is established Were as a result found a number of unknown before effects It was succeeded to establish two functions in which all codons reassignment participate in mitochondrial genetic codes human and other organisms and also essential distinction in integrated characteristics of such codes by comparison with a standard code Other properties of structure of the genetic code following from the received results are established also On the basis of the constructed theory the problem of calculating the genetic code was set in 1992 and the first complete publication was published recently 26